A Treatable Rare Cause of Progressive Ataxia and Palatal Tremor. (17th May 2018) - Rossi, Malco; Cesarini, Martin; Gatto, Emilia M.; Cammarota, Angel; Merello, Marcelo
Background: Cerebrotendinous xanthomatosis is a rare autosomal recessive neurometabolic disorder characterized by chronic diarrhea, tendon xanthomas, juvenile cataracts, and neurological symptoms. Case Report: An adult patient with cerebrotendinous xanthomatosis exhibited ataxia and palatal tremor in the absence of tendon xanthomas and cataracts. Discussion: The importance of this case resides on the fact that cerebrotendinous xanthomatosis should be considered as a possible etiology of the syndrome of progressive ataxia with palatal tremor, even in the absence of tendon xanthomas and cataracts. Early diagnosis is critical to the institution of specific treatment with chenodeoxycholic acid.